Dinamika Zakat Maal di Era Digital: Kajian Literatur Hadis dan Strategi Adaptasi dalam Masyarakat Urban - Abdul Chadjib Halik; Zulfahmi Alwi; Abdul Rahman Sakka (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study explores the dynamics of zakat maal in the digital era, particularly within urban communities, through a literature review of hadith and technological adaptation strategies. Zakat maal, as one of the pillars of Islam, plays a crucial role in wealth redistribution and reducing social inequality. However, technological advancements have introduced new challenges and opportunities in zakat maal practices. This research employs a literature review of hadith to understand the theological foundation of zakat maal and analyzes case studies on the implementation of technology in zakat payments. The findings indicate that digitalization of zakat maal can enhance community participation, transparency, and efficiency in zakat distribution. Nonetheless, challenges such as digital literacy, technology access, and regulatory policies still need to be addressed. This study contributes to the understanding of zakat maal adaptation in the digital age and provides practical recommendations to improve awareness and acceptance of technology in zakat among urban communities. The results are expected to support the development of more inclusive and effective zakat policies and practices in the future.